Plataforma interativa de aprendizagem de programação voltada a disseminação do pensamento computacional utilizando robótica remota - Barcaroli, Velcir (2017)
Computational thinking in the contemporary world is a fundamental skill for anyone, not just computerscientists. Along with reading, writing, and arithmetic, it is suggested to adding computational thinkingto each child’s analytical ability. Pedagogical Robotics, which is characterized by learning environmentswhere the student can assemble and program a robot, could be a way to disseminate Computational Thinking. It is believed that this work will make possible young students the contact with current anddigital technologies, favoring the development of computational thinking among them. The objective of this study is to build a platform that allows students of primary and secondary education, as a means to spread the computational thinking, can use remote programming of a robot arm via the internet sothat. In this research are presented technologies and tools that enable the development of a remote programming platform of a robotic arm. The platform divided into four modules: the physical partcomprising robotic arena and arm, image module responsible for generating the videos, user interface module that allows the robot to be programmed on any computer connected to the internet and theintegration module responsible For managing the entire platform. In conducting tests with volunteers, the platform proves to be challenging, provoking in them a sense of competition, fun and motivation to achieve the proposed challenges. This environment allows students to learn robotics concepts and interact interactively with a robot, programming it and understanding it, without having to have a robotic device.